A 1-D non-isothermal dynamic model for the thermal decomposition of a gibbsite particle - Amiri, Amirpiran; Bekker, Andrey; Ingram, G.; Livk, Iztok; Maynard, Nicoleta (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2013)
A 1-D mathematical model describing the thermal decomposition, or calcination, of a single gibbsite particle to alumina has been developed and validated against literature data. A dynamic, spatially distributed, mass and energy balance model enables the prediction of the evolution of chemical composition and temperature as a function of radial position inside a particle. In the thermal decomposition of gibbsite, water vapour is formed and the internal water vapour pressure plays a significant role in determining the rate of gibbsite dehydration. A thermal decomposition rate equation, developed by closely matching experimental data reported previously in the literature, assumes a reaction order of 1 with respect to gibbsite concentration, and an order of −1 with respect to water vapour pressure. Estimated values of the transformation kinetic parameters were k0 = 2.5 × 1013 mol/(m3 s) for the pre-exponential factor, and Ea = 131 kJ/mol for the activation energy. Using these kinetic parameters, the gibbsite particle model is solved numerically to predict the evolution of the internal water vapour pressure, temperature and gibbsite concentration. The model prediction was shown to be very sensitive to the values of heat transfer coefficient, effective diffusivity, particle size and external pressure, but relatively less sensitive to the mass transfer coefficient and particle thermal conductivity. The predicted profile of the water vapour pressure inside the particle helps explain some phenomena observed in practice, including particle breakage and formation of a boehmite phase.